Primary Angiosarcoma of the Breast after Bilateral Breast Reduction - Justus Philip; Elizabeth Bender; Kristy Waite (Case Reports in Surgery)
Angiosarcoma of the breast is a rare malignancy of endothelial cell origin, representing less than 1% of all breast malignancy. Primary angiosarcomas can occur in the setting of chronic lymphedema, but it also may occur spontaneously without any preceding treatment. Surgery is the primary therapeutic intervention for breast angiosarcomas with radiation and chemotherapy as adjuvant treatment. Angiosarcomas are aggressive and tend to have a high risk of local and metastatic recurrence. We present a case of primary angiosarcoma that developed in a patient who had bilateral breast reduction surgery in the past.